Validity of equivalent square field concept in small field dosimetry. Issue 6 (7th April 2022) - Das, Indra J.; Dogan, Serpil K.; Gopalakrishnan, Mahesh; Ding, George X.; Longo, Mariaconcetta; Franscescon, Paolo
Abstract: Purpose: The equivalent square (ES) concept has been used for traditional radiation fields defined by the machine collimating system. For small fields, the concept S clin was introduced based on measuring dosimetric field width (full‐width half maximum, FWHM) of the cardinal axis of the beam profiles. The pros and cons of this concept are evaluated in small fields and compared with the traditional ES using area and perimeter (4A/P) method based on geometric field size settings, for example, light field settings. Methods: One hundred thirty‐seven square and rectangular fields from 5–50 mm with every possible permutation (keeping one jaw fixed and varying other jaw from 5 to 50 mm) were utilized to measure FWHM for the validation of S clin . Using a microSilicon detector and a scanning water tank, measurements were performed on an Elekta (Versa) machine with Agility head and a Varian TrueBeam with different MLC/Jaw design to evaluate the S clin concept and to understand the effect of exchange factor in small fields. Field output factors were also measured for all 137 fields. Results: The data fitting for fields ranging from 5–50 mm between the traditional 4A/P method and S clin shows differences and indicates a linear relationship with distinct separation of slope for Elekta and Varian machines. For Elekta Agility machine ES based on 4A/P < S clin and for the VarianTrueBeam 4A/P > S clin for square fields. Our measured data show that both methods are equally valid but does vary by the machine design. The field output factor is dependent on the elongation factor as well as machine design. For fields with sides ≥10 mm, the exchange factor is nearly identical in both machines with magnitude up to 4%, which is close to measurement uncertainty (±3%), but for small fields (< 10 mm), the Elekta machine has higher exchange factors compared to the Varian machine. Conclusion: The results demonstrate that the two concepts for defining equivalent field ( S clin and 4A/P) are equivalent and can be directly related through an empirical equation. This study confirms that 4A/P is still valid for small fields except for very small fields (≤10 mm) where source occlusion is a dominating factor. The S clin method is potentially sensitive to measurement uncertainty due to measurement of FWHM which is machine‐, detector‐ and user‐dependent, while the 4A/P method relies mainly on geometry of the machine and has less dependency on type of machine, detector, and user. The exchange factors are comparable for both types of machines. The conclusion is based on data from an Elekta with Agility head and a Varian TrueBeam machine that may have potential for bias due to light field/collimator set up and alignment. Care should be taken in extrapolating these data to any other machine.